Performance Effectiveness of Civil Servants Police Unit in Controlling Street Vendors in Bandung City - Wiguna, Willy; Muhtar, Entang Adhy; Ismanto, Slamet Usman (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2025)
This study examines the performance of the Civil Servant Police Unit (Satpol PP) in Bandung City in controlling street vendors (PKL). The issue focuses on the high rate of public order violations by PKL despite existing regulations. This qualitative descriptive research utilized in-depth interviews for data collection. The findings reveal that the effectiveness of Satpol PP's performance can be assessed through three approaches: goal-oriented, resource-based, and stakeholder-focused. The goal-oriented approach indicates the achievement of a Public Order Index of 6.90 in 2024, aligning with the vision of a livable city. The resource-based approach highlights the efficient management of funding, amounting to IDR 28.8 billion, and human resources predominantly from Grade II. Meanwhile, a public perception survey rated the performance as "orderly," with a satisfaction ratio of 0.71. Recommendations include enhancing human resource training, strengthening regulations, and adopting technology for real-time monitoring of PKL activities. Emphasis on collaboration between local government, community, and other stakeholders is crucial for sustaining effectiveness. This study underscores the importance of a comprehensive approach to improving public services and supporting Bandung City's vision as a livable city.